Determinants Factors To Firm Value On Manufacturing Company Listed On The Stock Exchange Indonesa - Dikdik Harjadi; Jaelani Jaelani; Dewi Fatmasari (UIN Siber Syekh Nurjati Cirebon, 2021)
The study aims to analyze the influence of determining factors to the firm value, the gap phenomenon that the increase in the stock price index of the manufacturing sector is only slightly compared to the IDX Composite. Whereas the manufacturing sector are expected to have strong financial performance in contributing to the economy. This research uses a quantitative approach, with purposive sampling, obtained a sample of 110 the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2010 - 2017, using multiple linear regression. The results show that the dividend policy and profitability affect the firm value, while managerial ownership and board size are the opposite. This finding is interesting, the increase in the firm value of manufacturing sector is determined by dividend and profit policies, not manager incentives and monitoring of the board, because in general the company's the managers and board are held by the majority shareholder.Â Keywords: firm value, dividend policy, managerial ownership, board size, and profitability.